Immunosupressive treatment with cyclosporin-A for a patient with hypoplastic myelodisplastic syndrome: a case report - Pavkovic M; Jovanovic R; Petrusevska G; Cevreska L; Stojanovic A (Македонска академија на науките и уметностите, Одделение за биолошки и медицински науки = Macedonian Academy of Sciences and Arts, Section of Biological and Medical Sciences, 2011)
Backgraound: Imunosupressive therapy with antithymocyte globulin (ATG), cyclosporine (CsA) or both has been shown to induce haematological responses in a subset of patients with myelodysplastic syndromes (MDS), in particular in the hypocellular form of MDS. Case report: We report our first case with hypocellular MDS treated with CsA. A 54-year-old female referred to our Department due to weakness and severe pancytopenia. Hypocellular form of MDS was diagnosed after bone marrow biopsy. Treatment with CsA was started one year after diagnosis. Treatment with CsA resulted in clinical improvement, a very good partial haematological response, resolution of transfusion requirement and an increase in bone marrow cellularity. Conclusions: In our experience, immunosuppressive treatment with CsA and/or ATG could be an alternative for patients with hypoplastic MDS for whom there is no possibility of allogenic bone marrow transplantation as only curative therapy.